Evaluation Evaluating the Duration and Intensity of MathQuest Game Use in Mathematics Learning: A Comparative Study of Elementary Students’ Engagement and Participation - Alfiana Sahraini; Syaharuddin; Vera Mandailina (MIMBAR PGSD Undiksha, 2025)
The problem underlying this study is the suboptimal use of instructional duration in enhancing student engagement and participation, particularly in the context of game-based learning. Moreover, there is a lack of research that specifically examines the impact of short-duration differences on student engagement patterns, both individually and in groups. Therefore, this study aims to compare the levels of student engagement and participation in mathematics learning based on differences in duration and intensity of MathQuest game usage. This study employed a quantitative approach with an experimental design. The research subjects were 49 sixth-grade elementary school students divided into two groups, namely Class A and Class B. Data were collected using observation sheets and pre-test and post-test instruments developed based on validated indicators of student engagement (X1) and participation (X2). The collected data were analyzed using descriptive statistics and the Independent Sample t-test to determine the significance of differences between the two groups. The analysis results showed significance values for individual engagement (0.977), group engagement (0.084), individual participation (0.834), group participation (0.834), and participation within the group (0.145), all of which were greater than 0.05, indicating no significant differences in the average levels of engagement and participation between students in Class A and Class B, both individually and in groups. Although there were slight variations in mean scores and standard deviations, these differences were not substantial enough to influence the conclusions of the study.